Recombinant Limb Assay as in Vivo Organoid Model - García-García, Roberto Damián; Garay-Pacheco, Estefanía; Marín-Llera, Jessica Cristina; Chimal-Monroy, Jesús (Frontiers in Cell and Developmental Biology, 2022)
Organ formation initiates once cells become committed to one of the three embryonic germ layers. In the early stages of embryogenesis, different gene transcription networks regulate cell fate after each germ layer is established, thereby directing the formation of complex tissues and functional organs. To study the formation of organs, these events can be modeled in vitro by creating organoids from induced pluripotent, embryonic, or adult stem cells. Under these conditions, the induced cells are guided down the developmental pathways as in embryonic development, resulting in an organ of a smaller size that possesses the essential functions of the organ of interest. Although the formation of organoids is widely studied, the formation of skeletal elements in an organoid model has not yet been possible. Therefore, we suggest that the formation of skeletal elements using the recombinant limb (RL) assay system can serve as an organoid in vivo model. RLs are formed from undissociated or dissociated-reaggregated undifferentiated mesodermal cells introduced into an ectodermal cover obtained from an early limb bud. Next, this filled ectoderm is grafted into the back of a donor chick embryo. Under these conditions, the cells can receive the nascent embryonic signals and develop complex skeletal elements. We propose that the formation of skeletal elements induced through the RL system may occur from stem cells or other types of progenitors, thus enabling the study of the formation of these complex structures from these cells for the first time in vivo.